The effect of creative writing activities on pre-service teachers' narrative text composing skills - Eylem Ezgi Ahıskalı; Saadet Maltepe (Journal of Pedagogical Research, 2023)
This study aims to determine the effect of creative writing activities based on narrative expression on pre-service teachers' ability to create narrative texts. The research was structured with a mixed research method in which qualitative and quantitative research methods were used together. Quantitatively, the study employed a pre-test post-test one-group quasi experimental design, whereas qualitatively, a case study design was employed. The sample group was composed of 20 pre-service teachers enrolled in the Turkish Language Teaching Program at a state university during the fall semester of the 2021-2022 academic year. An analytical rubric consisting of nine sections was developed for evaluating narrative texts written by pre-service teachers to collect quantitative data. A structured interview form consisting of five questions was also used to interview pre-service teachers in the study group about their opinions on the implementation process. Qualitative data were analyzed using the content analysis technique, while quantitative data were analyzed descriptively. The study concluded that narrative expression-based creative writing activities benefited Turkish pre-service teachers' abilities to create narrative text, resulting in an increase in narrative text elements. Also, creative writing activities made the story writing process enjoyable for pre-service teachers and had a positive influence on their views on the application process. The conclusion was also drawn that story elements were incorporated into narrative texts through creative writing techniques.